Development Of Cultural Frameworks In Radio Broadcasting In Slovakia - Lehoczká, Viera (Communication Today, 2025)
In August 2010 there elapsed 84 years from a successful start of regular radio broadcasting in Slovakia, under the brand “Radiojournal”. In the process of cultural-historical development in our country, the Slovak Radio has established itself as a representative of the unique cultural and artistic values in the line of mass media communication to overcome the complex evolution, whereas it has lost no importance not even under the inﬂuence of competing forms of mass media (modern press, television and Internet). Its fruitful history started with its foundation as a part of the Czechoslovak Society Radiojournal, later continued as an institution of the independent Slovak State in World War II, and then in the socialist Czechoslovakia too, and ﬁ nally it established itself as a considerable public-service institution after 1990. At present, since January 2011 it has been operating and broadcasting in a merged public-service institution RTVS in a common body with the Slovak Television.The Slovak Radio in a line of its forerunners has gradually created conditions for the nationwide providing of audio-acoustic services for public in the sphere of radio broadcasting in the sense of a national, independent, informational, cultural and educational institution. Inﬂ uence of the Slovak Radio, which contributed to the cultural and civilization development, may be in this connection understood as a speciﬁ c cultural phenomenon in the sense of emancipation anchor attaching of the radio in the culture as expression of cultural reference to life. During more than eighty years of its existence, the mission of the oldest Slovak electronic medium was changed and amended, particularly by broadening its technical capabilities and programme forms. In its broadcasting, it systemically and comprehensively surveys the cultural events in its entire scope, where the expressive potential of high quality music and a literary word of sound-modulated communication have its irrecoverable position. A signiﬁ cant phenomenon of the Slovak Radio as a part of the current culture during its historical development has penetrated very intensively into the society, and even now it affects all spheres of social life, and opens the fundamental question of synchronizing them with the cultural past and national speciﬁ cities in the context of moral and ethical responsibility and also high value criteria. The historical development of broadcasting has created supporting pillars for a balanced cultural tradition of public service in national and European level. In terms of cultural and historical signiﬁ cance the Slovak Radio played a dominant role with music and dramatic ensembles, but not only as disseminators of culture, but also as signiﬁ cant components of increase of audience. Culture and art keep their positions in radio communications just through SR broadcasting. During eighty years of its existence, the public-service Slovak Radio built a gradual transformation of its own wide-ranging backstage and creative broadcasting centres, whether dramatic ensembles or musical groups, in a course of program content production systematically implementing various genres and forms of broadcasting. Inﬂ uence of the Slovak Radio contributed to the cultural and civilization development and in this context it can be understood as a speciﬁc cultural phenomenon ﬁ rmly integrated into a cultural competence for life. High-quality and successful program structure of the Slovak Radio stays on the use of long-term programming experience of Slovak radio-broadcasting and on the tradition of the predecessors and is destined to balanced offer of programs in relation to majority and minority groups of listeners. Reaching and acquiring the young population is one of the latest trends in the public-service Slovak Radio practice. Importance of the Slovak Radio for its listeners is its value orientation for culture and education above all regarding a commercial offer at dual radio market in Slovakia. At the Slovak market, the Slovak Radio maintains a distinct cultural-mediation position as a broad area for the time-tested quality of the broadcasting.